2006
DOI: 10.1176/appi.ajp.163.3.418
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Real-World Functional Performance in Schizophrenia Subjects: Correlations With Cognition, Functional Capacity, and Symptoms

Abstract: Real-world adaptive life skills are predicted by neuropsychological performance, symptoms, and functional capacity. Neuropsychological performance contributes little to the prediction of real-world performance after accounting for functional capacity. In some domains, negative and depressive symptoms influenced real-world performance while not relating to functional capacity or neuropsychological performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
473
6
16

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 683 publications
(529 citation statements)
references
References 27 publications
34
473
6
16
Order By: Relevance
“…For example, the brevity of the UPSA (i.e., 30 minutes) makes it preferable to lengthy batteries assessing multiple cognitive domains. Indeed recent research (Bowie et al, 2006;Keefe et al, 2006) has indicated that the prediction of real-world outcomes is not enhanced by cognitive performance when scores on the UPSA are considered. In addition, unlike assessments of global cognitive functioning (e.g., DRS) healthcare professionals do not need specialized training in order to administer the UPSA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the brevity of the UPSA (i.e., 30 minutes) makes it preferable to lengthy batteries assessing multiple cognitive domains. Indeed recent research (Bowie et al, 2006;Keefe et al, 2006) has indicated that the prediction of real-world outcomes is not enhanced by cognitive performance when scores on the UPSA are considered. In addition, unlike assessments of global cognitive functioning (e.g., DRS) healthcare professionals do not need specialized training in order to administer the UPSA.…”
Section: Discussionmentioning
confidence: 99%
“…Participants receive scores for each of the 5 subscales (range = 0-20), which are summed to create a summary score ranging from 0 to 100. Previous research has established that the UPSA is highly related to neurocognitive functioning (Bowie et al, 2006;Twamley et al, 2002) and performance on a number of functional abilities (Bowie et al, 2006). ' Dementia Rating Scale (DRS;Mattis, 1973) was administered as an assessment of overall cognitive functioning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While it could be argued that the generalizability of this method may be limited because there may be differences between patients' competence or capacity (i.e., what they can do) and performance in the real world (i.e., what they actually do), functional capacity may also be less likely to be influenced by factors outside the control of treatment interventions (e.g., disability status, familial financial resources). In fact, we have demonstrated that functional capacity (what a patient can do), based on performance in a laboratory setting, is moderately correlated with real world deployment of those skills, but strongly correlated with performance on measures of cognitive functioning (Twamley et al, 2002;Bowie et al, 2006).…”
Section: Introductionmentioning
confidence: 89%